Role of social media marketing activities in China’s e-commerce industry: A stimulus organism response theory context - Sohaib, Muhammad; Safeer, Asif Ali; Majeed, Abdul (Frontiers in Psychology, 2022)
Social media marketing has become one of the most significant growth paths for many businesses in today’s world. However, many companies are still unclear about using social media marketing to get their advantages, particularly in an e-commerce environment. In this background, this study is proposed to examine the effects of social media marketing activities (SMMAs) (interactivity, informativeness, word-of-mouth-WOM, personalization, and trendiness) on relationship quality, such as commitment, trust, and satisfaction in order to predict consumers’ online repurchase intentions in China’s e-commerce environment. This study proposed a theoretical model by using the stimulus-organism-response (S-O-R) theory. Using a structured questionnaire and purposive sampling, this study examined the responses of 403 consumers through partial least square-structural equation modeling. The findings discovered that SMMAs significantly strengthen the relationship quality factors, such as commitment, trust, and satisfaction, which in turn positively increase consumer online repurchase intentions in China’s e-commerce industry. This is novel research that contributes to the S-O-R theory and provides several managerial guidelines that assist managers in improving their business performance in the e-commerce industry. This research also highlighted some limitations.